Fostering Critical Thinking through Digital Game-Based Learning: A Case Study - Katrin Pepita; Sri Setyarini (Universitas Nusantara PGRI Kediri, 2026)
Critical thinking is increasingly recognized as a vital skill for young learners in the twenty-first century. This qualitative case study investigated how online educational games fostered critical thinking in an eight-year-old English learner. Data were collected through participatory observation, semi-structured interviews, and screen recordings, and were analyzed thematically using Facione’s framework. The results indicate that game-based tasks activated several dimensions of critical thinking, particularly interpretation, analysis, inference, and evaluation, through interactive and meaningful engagement. The study also highlights the important role of adult scaffolding in supporting learners’ questioning, clarification, and reflective decision-making during gameplay. These scaffolds enabled the learner to connect prior schemas with new information and refine decisions. The study offers preliminary insights into how critical thinking in young learners may be understood from both cognitive and sociocultural perspectives within digital learning environments. In practice, the findings suggest that online educational games can support the development of critical thinking when accompanied by appropriate facilitation by teachers or parents. However, the study is limited by its single-case design; therefore, future research is recommended to investigate digital game-based learning and critical thinking across broader groups of participants and educational contexts.